SOSIALISASI PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL (PPKS) DI SEKOLAH TINGGI ILMU EKONOMI LPI MAKASSAR - Baso Sardjan; Indah Ramadhani Amir; Muh. Anzhari; Muhammad Isra’Chikah Arfah; April Sisilia Bura Tasik; Taswin Taswin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The problem of sexual violence requires special handling. In contrast to the handling of other (especially criminal) cases which are usually oriented towards punishing the perpetrator, the handling of sexual violence cases is different. In Permendikbudristek Number 30 of 2021, it is stated that the handling of sexual violence cases includes (1) treatment, (2) protection, (3) imposition of administrative sanctions, and (4) recovery of victims. The principle of handling victims of sexual violence is to take the victim's perspective and not repeat cases. Having a victim perspective means that treatment must prioritize the victim's recovery, according to their needs, focus on their safety and comfort, and with the victim's consent. However, the existing reality shows that the community's understanding of the problem of sexual violence still needs to continue to be improved. An example is the university community's understanding of sexual violence which has various types. In Permendikbudristek Number 30 of 2021, it is stated that there are 21 types of acts that fall into the category of sexual violence. The results of reflection on Permendikbudristek Number 30 in 3 universities (State University of Malang/UM, University of North Sumatra/USU, and University of Palangkaraya/UPR) showed that 77% of respondents admitted to experiencing or knowing that there was sexual violence on their campus. Apart from that, it turned out that 9% of respondents admitted that they had only just become aware of the various types of violence and felt that they had committed sexual violence.